Identifikasi Genetik Ikan Gabus Asal Merauke dengan Menggunakan Fragmen Gen Sitokrom Oksidase Sub Unit I - Muhammad Dailami; Ating Yuniarti; Dandi Saleky; Abdul Hamid A. Toha (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Efforts to cultivate snakehead fish (Chanidae) still experience many problems, especially the availability of high-quality fry. To improve the quality of fry, improving the quality of broodstock is important. Genetic factors play an important role in the selection and breeding of snakehead fish parents. Therefore, it is necessary to explore sources of superior parents with good genetic characteristics. To achieve this goal requires studies from various fields such as ecology, biology, and genetics. Genetic studies can be started by examining the identity and relationships of snakehead fish from Merauke, as a first step in finding a source of germplasm that has high diversity. The aim of this research is to analyze the cytochrome oxidase subunit 1 (COI) gene fragment of snakehead fish from Merauke, Papua. DNA isolation was carried out using the Promega kit with standard protocols, amplification of the COI gene with primers F2 and R2 with the Go Taq Green amplification kit. A total of 653 base pairs of the COI gene fragment were obtained from the sequencing process, with a nucleotide composition of T (29.9%), C (28.8%), A (24.0%), G (17.3%). BLAST results on the NCBI database show that this sequence has 100% similarity to the Channa striata sequence from Papua with sequence ID OQ405388.1. This shows that the identification results of the snakehead fish from Merauke are Channa striata. Phylogenetic tree analysis also showed consistent results, namely the formation of a clade that was the same as the Channa striata fish group derived from GenBank data.